EMU and the cyclical behavior of fiscal policy: A suggested interpretation - Oliver Landmann (University of Freiburg, Department of International Economic Policy (iep), 2014)
Fiscal policy is widely criticized for its failure to act as a stabilizing countercyclical force in the European Monetary Union. Two periods should be distinguished: Prior to the Financial Crisis of 2008, when monetary policy had traction to pursue stability for the aggregate eurozone, fiscal policies failed to contain macroeconomic divergence across the currency area. After the crisis, when interest rates had hit the zero lower bound, widespread fiscal austerity exacerbated the persistent recession. The paper proposes a minimal model of decentralized fiscal policymaking in a monetary union. The model is used to interpret policy behavior in both periods. The analysis points to a pro-cyclical bias and suggests a need for coordination.
Keywords: E5; E6; F41; F42; 330; Fiscal Policy; Monetary Union; Multiplier; International Policy Coordination; Monetary-Fiscal Policy Interaction